1999
DOI: 10.1038/sj.bmt.1702058
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6 infection inhibits specific lymphocyte proliferation responses and is related to lymphocytopenia after allogeneic stem cell transplantation

Abstract: Summary:Human herpesvirus 6 (HHV-6) infection and the HHV-6-specific lymphocyte proliferation response were studied longitudinally in 24 patients in the first 3 months after allogeneic stem cell transplantation (allo-SCT). HHV-6 DNAemia was analyzed by a nested PCR method, and the HHV-6-specific lymphocyte proliferation responses were evaluated with a standard lymphocyte proliferation assay. All patients who responded to HHV-6 GS (variant A) antigen also responded to HHV-6 Z29 (variant B) antigen, and a respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…For example, in patients after stem cell transplantation, HHV-6 and CMV reactivation were associated with lymphopenia and reduction in proliferative responses to HHV-6 and CMV [38,39]. However, these results were interpreted in contrasting terms for the two herpesviruses: HHV-6 was supposed to be the causal agent for an immunosuppression that permitted reactivation of this virus and of CMV [38,39]. Only recently, the straightforward alternative explanation has been offered that lymphopenia-associated deficiencies in T cells specific for either virus could be the common cause why either virus may reactivate in transplant patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients after stem cell transplantation, HHV-6 and CMV reactivation were associated with lymphopenia and reduction in proliferative responses to HHV-6 and CMV [38,39]. However, these results were interpreted in contrasting terms for the two herpesviruses: HHV-6 was supposed to be the causal agent for an immunosuppression that permitted reactivation of this virus and of CMV [38,39]. Only recently, the straightforward alternative explanation has been offered that lymphopenia-associated deficiencies in T cells specific for either virus could be the common cause why either virus may reactivate in transplant patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of HHV-6 in the peripheral blood may correlate with delayed platelet engraftment, as reported by others. 4,24 Isomura et al 25 also reported that the direct effect of HHV-6 on hematopoietic progenitors is one of the major causes of suppression of thrombopoiesis. To date, Bone Marrow Transplantation the pathogenic potential of HHV-6 in SCT recipients is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Since post-transplant EBV-induced lymphoproliferative disorders (PT-LPD) may arise in the period between the initiation of engraftment and 6-8 mouths post transplant, at which time many patients have defects in T cell function, 4 we should keep following-up all the patients carefully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,6 Infection of these cells leads to alteration and modification of immune responses, further facilitating viral replication and creating an environment adept for further viral reactivation. 2,6 Because of the exposure of the recovering immune system to this massive amount of HHV6 Ags, a large number of cells become activated; including the few allo-reactive T cells. 2 This imbalance in immune response promotes the development of GVHD, further enhanced by upregulation of HLA class I and II molecules by the virus.…”
mentioning
confidence: 99%